Standard of proof on fraud in civil proceedings and voidable construction contract - Azman Hamzah, 1984-; Jamaluddin Yaakob, supervisor; Fakulti Alam Bina (2010)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan) - Universiti Teknologi Malaysia, 2010